UPAYA DINAS PENGELOLAAN PASAR DAN KEBERSIHAN KABUPATEN BUNGO DALAM MENGATASI TINGGINYA TUNGGAKAN RETRIBUSI DI PASAR BUNGUR KABUPATEN BUNGO - Siti Maryam; Akhmad Legianto (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2021)
The year-end report from the Market Management and Hygiene Service stated that user fees from the market are one of the local revenue sources that generate the most user fees. However, in achieving its realization, it is very difficult to achieve, this can be seen from the receipt of the Bungur Bungur market levy for the last 2 years. Bungur Market retribution collection is not optimal, it can be seen in the table above from 2013-2014 the realization of market retribution in Bungo Regency, especially Bungur Market, has never met the target. The method used in this study is a descriptive method with a qualitative approach. The method used to find informants using "purposive sampling". The results of the study found that the efforts made by the Department of Market Management and Hygiene of Bungo Regency in overcoming the high arrears of levies were holding outreach to kiosk owners or occupants about the importance of paying retribution for regional development, collecting door to door retribution, empowering the Regional Enforcement Work Unit. Regional regulations to help collect levies, provide strict sanctions for non-paying retribution obligations. The obstacles faced by the Market Management and Hygiene Service in overcoming the high arrears of retribution at the Bungur Market, Bungo Regency, include the absence of strict sanctions for non-paying levies, the large number of owners who are given placement permits by the Bungo Regency Market Management and Hygiene Service to rent back. to other people or other traders so that the tenant feels no obligation to pay levies and the economic situation has not been stable, especially for the city of Muara Bungo in the last 2 (two) years